Turning Wood Autohydrolysate Directly into Food Packing Composite Films with Good Toughness - YaJie Hu; YaShuai Niu; GenQue Fu; PanPan Yue; MingFei Li; Feng Peng; RunCang Sun (International Journal of Polymer Science)
Bio-based composite films were produced by incorporating wood autohydrolysate (WH), chitosan (CS), and cellulose nanocrystals (CNC). In this work, WH was directly utilized without further purification, and CNC was introduced as the reinforced material to prepare WH-CS-CNC composite films with excellent properties. The effects of CNC on the properties of WH-CS-CNC composite films were investigated by characterizing their structures, mechanical properties, oxygen barrier, and thermal stability properties. The results suggested that CNC could improve tensile strength of the composite films, and the tensile strain at break could be up to 4.7%. Besides, the oxygen permeability of the prepared composite films could be as low as 3.57 cm3/day·m2·kPa, making them suitable for the food packaging materials. These above results showed that the addition of CNC is an effective method to enhance the toughness of composite films. In addition, WH-CS-CNC composite films have great potential in the field of sustainable food packing materials.